Association Between the Amount of Limb Lengthening and Hip Range of Motion After Total Hip Arthroplasty. Issue 6 (15th March 2022) - Kawai, Toshiyuki; Goto, Koji; Kuroda, Yutaka; Okuzu, Yaichiro; Matsuda, Shuichi
Abstract : Aims: The relationship between prosthetic position and range of motion (ROM) after total hip arthroplasty (THA) has been rigorously examined. However, the effects of limb lengthening on postoperative hip ROM remain unclarified. We aimed to examine the effect of limb lengthening on hip ROM after THA. Methods: We retrospectively reviewed the data from 120 patients who underwent unilateral THA. Univariate and multivariate regression models were used to evaluate the effects of the following patient- and surgery-related covariates on hip flexion ROM at 3, 6, and 12 months after THA: age, sex, body mass index, diagnosis, preoperative University of California Los Angeles activity score, preoperative Oxford Hip Score, preoperative flexion ROM, amount of leg lengthening, cup inclination, and cup anteversion. Results: A large preoperative hip flexion ROM was the strongest predictor of a large hip flexion ROM at 12 months after THA (standardized coefficient: 0.519, P < 0.0001). A larger amount of leg lengthening was associated with a smaller postoperative hip flexion ROM (standardized coefficient: −0.159, P = 0.039), and male sex was another predictor of a smaller postoperative hip flexion ROM (standardized coefficient: −0.204, P = 0.014). Cup inclination ( P = 0.99) and anteversion ( P = 0.18) were not significantly associated with hip flexion ROM at 12 months after THA. Discussion: A large amount of limb lengthening was associated with decreased hip flexion ROM after THA. In THA, minimizing the leg length discrepancy is important; however, the postoperative improvement in hip flexion ROM may be limited when a large amount of leg lengthening is needed.